Repint of "Reframing autism as a behavioral syndrome and not a specific mental disorder: Implications of genetic and phenotypic heterogeneity". (June 2018) - Tordjman, S.; Cohen, D.; Anderson, G.M.; Botbol, M.; Canitano, R.; Coulon, N.; Roubertoux, P.L.
Highlights: A literature review of genetic disorders associated with autism is presented here. This review shows a high genetic and etiological heterogeneity of autism. Underlying mechanisms possibly leading to a similar autism phenotype are discussed. Autism can be viewed as a behavioral syndrome rather than a specific categorical mental disorder. A multidimensional, dynamic and transnosographic approach is necessary. Abstract: Clinical and molecular genetics have advanced current knowledge on genetic disorders associated with autism. A review of diverse genetic disorders associated with autism is presented and for the first time discussed extensively with regard to possible common underlying mechanisms leading to a similar cognitive-behavioral phenotype of autism. The possible role of interactions between genetic and environmental factors, including epigenetic mechanisms, is in particular examined. Finally, the pertinence of distinguishing non-syndromic autism (isolated autism) from syndromic autism (autism associated with genetic disorders) will be reconsidered. Given the high genetic and etiological heterogeneity of autism, autism can be viewed as a behavioral syndrome related to known genetic disorders (syndromic autism) or currently unknown disorders (apparent non-syndromic autism), rather than a specific categorical mental disorder. It highlights the need to study autism phenotype and developmental trajectory through a multidimensional, non-categorical approach with multivariate analyses within autism spectrum disorder but also across mental disorders, and to conduct systematically clinical genetic examination searching for genetic disorders in all individuals (children but also adults) with autism.